Kinetic-Catalytic-Spectrophotometric Determination of Ultra Trace Amounts of Palladium(II) by Its Catalytic Effect on The Oxidation of Naphthol Green B by Metaperiodate - KEYVANFARD, MOHSEN; REZAEI, B. (Asian Journal of Chemistry, 2010)
A new, simple, sensitive and selective catalytic spectrophotometric method was developed for the determination of ultra trace amounts of Pd(II).The method is based on the catalytic effect of palladium on the oxidation of Naphthol green B by metaperiodate. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of Naphthol green B at 710 nm with a fixed-time method. The decrease in the absorbance of Naphthol green B is proportional to the concentration of Pd(II) in concentration range 5.0-80.0 ng/mL, with a fixed time of 0.5-3.0 min from initiation of the reaction.The limit of detection is found to be 2.2 ng/mL Pd(II).The relative standard deviation of 20.0 and 60.0 ng/mL Pd(II) was 2.1 and 2.6 %, respectively. The proposed method was applied to the determination of palladium in water and synthetic samples.